PENGARUH PRODUKTIFITAS TENAGA KERJA TERHADAP PRODUKSI TANAMAN BAWANG MERAH (Allium Ascolonium L.) DI KEBUN PRAKTEK FAKULTAS TEKNOLOGI PANGAN DAN PERTANIAN UNIVERSITAS NUSA NIPA - Eus Raja, Yohanes; Noni, Sarlina; Otan Apelabi, Gabriel (Universitas Cokroaminoto Palopo, 2024)
Shallots (Allium Cepa L.) is one of the horticultural commodities that has an important role in the economy. Increasing shallot production is one of the main focuses in efforts to achieve food security and farmers' welfare. Labor is a very important production factor and needs to be taken into account in the production process and not only seen from the availability of labor but also its quality. The purpose of this study is to determine the Effect of Labor Productivity on the Production of Shallot Plants (Allium cepa L.) in the Practice Garden, Faculty of Agricultural and Fisheries Food Technology, University of Nusa Nipa. Based on the results of research on the Practice Garden of the Faculty of Agricultural and Fisheries Food Technology, University of Nusa Nipa, the conclusion was obtained that Labor Productivity has a positive effect on the production of shallot plants This means that every increase or performance of Labor Productivity will increase crop yields or onion crop production. This is reinforced and supported by the value of sig. smaller than the alpha value of 0.000 < 0.05 This means that Labor Productivity has a positive and significant effect on the production of shallot crops. Furthermore, it can be seen that the result of t calculation is greater than the t of the table, which is 5,346 > 1,701, meaning that H0 is rejected and Ha is accepted. So this shows that the Productivity of Labor in UNIPA's FTP3 practice gardens has